THE INTEGRATION OF ISLAMIC VALUES IN IMPLEMENTATION OF LEARNING ENGLISH: ISLAMIC EDUCATION STUDENTS PERSPECTIVE - Mochlis Eko Wijayanto (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
The learning process at the University of Nurul Jadid must be guided by Trilogi Santri and Panca Kesadaran Santri formulated by the founder of the Nurul Jadid Islamic Boarding School Foundation. Thus, each learning program at the Faculty of Islamic Religion (FAI) of Nurul Jadid University must be able to produce teachers who can integrate Islamic values in their teaching, including learning English itself. To find out students as prospective teachers of Islamic religious education are able to integrate Islamic values into learning English. The problem in this research is, "how is the integration of Islamic values in learning English in the classroom through a religious approach?" This study is an empirical study (field research) in the form of descriptive methods. Data were analyzed using descriptive analysis method. The subjects of this study were 17 students majoring in Islamic religious education (PAI) in the academic year 2018/2019. Data collected using observation techniques. The results showed that in carrying out teaching practices in class English III, students of religious education (PAI) had a fairly good competence in integrating Islamic values into the teaching and learning process of English. It was demonstrated by 14 students (prospective teachers) who were able to integrate Islamic values in the learning material they applied. While the rest is only integrated into the opening and closing activities by saying Salam (Islamic greetings) and doing do'a (prayer).